2020
DOI: 10.1080/17455030.2020.1742401
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization-induced resonances with high-quality factor in a plasmonic chipscale ring-disk nanocavity

Abstract: Plasmonic resonators have drawn more attention due to the ability to confine light into subwavelength scale. However, they always suffer from a low quality (Q) factor owing to the intrinsic loss of metal. Here, we numerically propose a plasmonic resonator with ultra-high Q factor based on plasmonic metalinsulator-metal (MIM) waveguide structures. The resonator consists of a disk cavity surrounded by a concentric ring cavity, possessing an ultra-small volume. Arising from the plasmon hybridization between plasm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…By comparing their reported sensitivities for resonances, it can be concluded that sensitivities which are located in the visible light region are lower than those which are located in the near infra red region. (Zhang et al 2016), (Zhang et al 2020), (Wang et al 2019) and (Zhang et al 2018) have reported sensitivities of 596 nm/RIU, 579 nm/RIU, 623.8 nm/RIU, and 708 nm/RIU, respectively for their resonances in the visible light region. In order to extract the sensor parameters (S and FOM) for the total system equipped with two triangular silver patches inside the disk cavity (Fig.…”
Section: Sensitivity and Fom Of The Proposed Sensormentioning
confidence: 99%
See 2 more Smart Citations
“…By comparing their reported sensitivities for resonances, it can be concluded that sensitivities which are located in the visible light region are lower than those which are located in the near infra red region. (Zhang et al 2016), (Zhang et al 2020), (Wang et al 2019) and (Zhang et al 2018) have reported sensitivities of 596 nm/RIU, 579 nm/RIU, 623.8 nm/RIU, and 708 nm/RIU, respectively for their resonances in the visible light region. In order to extract the sensor parameters (S and FOM) for the total system equipped with two triangular silver patches inside the disk cavity (Fig.…”
Section: Sensitivity and Fom Of The Proposed Sensormentioning
confidence: 99%
“…The proposed waveguide system in this work has seven different geometrical parameters (Fig. 1b), which for brevity, the results of optimization for only two of them (x and 𝑔 2 ) was mentioned in subsection 3.3. unlike the simple MIM waveguide (which are applied in (Zhang et al 2018;Zhang et al 2020), with no additional cavity, that has only the geometrical parameter of width (width of insulator between two metal) to be evaluated, in this work, more decisive geometrical parameters on transmission spectra of the total system provided more variables to be applied in the optimization of the FOM of the resonances and resulted in FOM of 598.1 RIU −1 for the resonance of VL2.…”
Section: Sensitivity and Fom Of The Proposed Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…In order to make the refractive index change of the dielectric more sensitive, d 2 was set to 3740 nm. The performance of the sensor was evaluated by two factors, sensitivity (S) and FOM [29]:…”
Section: Sensing Performancementioning
confidence: 99%
“…3 Therefore, many plasmonic sensors have been investigated and proposed lately. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In waveguide-based plasmonic refractive index sensors, the sensing mechanism is through the interaction of their supported modes with their surrounding insulator test medium. 13 Unlike dielectric waveguides, where the light is steered through the total internal reflection (TIR) phenomenon, in plasmonic waveguides, electromagnetic waves are guided in the form of surface plasmon polaritons (SPPs) along the metal-dielectric interface.…”
Section: Introductionmentioning
confidence: 99%